Rancang Bangun Kunci Pintu Mobil Nirkabel Dengan Aplikasi Mobile Android - Aristama, Nicko Surya, Dr. Heru Supriyono, M.Sc (2017)
In the age of globalization is the development of formation technology increasingly sophisticated, especially of ronics with the development of information technology, especially in technology electronics it can improve performance nterms of efficiency and effectiveness. The electronics of the moment can be applied to various sectors. Among sectors of concern is the sector security in particular the safety of a car door. At this time of the security door is still a lot of relying on the security sistem of the car it self as a manuel and so it tohes a creativity that is to create a system tools to support the security of the car door in the wireless. In the study design construction loch this car be simulated and implemented. Design it up such a eviceesigned with the power supply input 12 VDC, 1,5 A to operate it. The components used is IC Atmega16 as icrocontroller,relays 12 VDC, resistor, capasitors, transistors, Led 5 mm, entral Loch the car, Horn as an alarm, the switch and the PCB and then are assembled in the PCB and in trials. Based ntesting that the hey tools the car towerh with the power supply at least 12 VDC, 1,5 A. Design it up lock the door car wirelessly using applications bluetooth could be in the remote using mobile phones with distance of 15 meters outdoors.